Nicotinamide Mononucleotide Administration Triggers Macrophages Reprogramming and Alleviates Inflammation During Sepsis Induced by Experimental Peritonitis - Cros, Cécile; Margier, Marielle; Cannelle, Hélène; Charmetant, Julie; Hulo, Nicolas; Laganier, Laurent; Grozio, Alessia; Canault, Matthias (Frontiers in Molecular Biosciences, 2022)
Peritonitis and subsequent sepsis, lead to high morbidity and mortality in response to uncontrolled systemic inflammation primarily mediated by macrophages. Nicotinamide adenine dinucleotide (NAD+) is an important regulator of oxidative stress and immunoinflammatory responses. However, the effects of NAD+ replenishment during inflammatory activation are still poorly defined. Hence, we investigated whether the administration of β-nicotinamide mononucleotide (β-NMN), a natural biosynthetic precursor of NAD+, could modulate the macrophage phenotype and thereby ameliorate the dysregulated inflammatory response during sepsis. To this purpose, C57BL6 mice were subjected to the cecal ligation and puncture (CLP) model to provoke sepsis or were injected with thioglycolate to induce a sterile peritonitis with recruitment and differentiation of macrophages into the inflamed peritoneal cavity. β-NMN was administered for 4 days after CLP and for 3 days post thioglycolate treatment where peritoneal macrophages were subsequently analyzed. In CLP model, administration of β-NMN decreased bacterial load in blood and reduced clinical signs of distress and mortality during sepsis. These results were supported by transcriptomic analysis of hearts and lungs 24 hours post CLP-induction, which revealed that β-NMN downregulated genes controlling immuno-inflammatory response and upregulated genes involved in bioenergetic metabolism, mitochondria, and autophagy. In the thioglycolate model, a significant increase in the proportion of CD206 macrophages, marker of anti-inflammatory M2 phenotype, was detected on peritoneal exudate macrophages from β-NMN-administered mice. Transcriptomic signature of these macrophages after bacterial stimulation, confirmed that β-NMN administration limited the pro-inflammatory M1 phenotype and induced the expression of specific markers of M2 type macrophages. Furthermore, our data show that β-NMN treatment significantly impact NAD+ metabolism.This shift in macrophage phenotype and metabolism was accompanied by a reduction in phagolysosomes acidification and secretion of inflammatory mediators in macrophages from β-NMN treated mice suggesting a reduced pro-inflammatory activation. In conclusion, administration of β-NMN prevented clinical deterioration and improved survival during sepsis. These effects relied on shifts in metabolism of organs that face up an increased energy requirement caused by bacterial infection and in innate immunity response, including reprogramming of macrophages from a highly inflammatory phenotype to an anti-inflammatory/pro-resolving profile.